Influence of Plant Growth Promoting Rhizobacteria, Compost, and Biochar of Azolla on Rosemary (Rosmarinus Officinalis L.) Growth and Some Soil Quality Indicators in a Calcareous Soil. Issue 2 (19th January 2019) - Sadegh Kasmaei, Leila; Yasrebi, Jafar; Zarei, Mehdi; Ronaghi, Abdolmajid; Ghasemi, Reza; Saharkhiz, Mohammad Jamal; Ahmadabadi, Zahra; Schnug, Ewald
ABSTRACT: In order to study the effect of plant growth promoting rhizobacteria (PGPR), Azolla compost and Azolla biochar on some soil quality indicators and rosemary growth, a greenhouse experiment was conducted in a completely randomized design with six replications. Treatments consisted of T1 (control), T2 (1% Azolla compost), T3 (1% Azolla biochar), T4 (PGPR ( P. fluorescens ), T5 (1% compost + PGPR) and T6 (1% biochar + PGPR). Rosemary growth parameters and nutrients concentration increased in all treatments compared to control. Treatments increased soil nutrient concentrations, soil microbial respiration (SMR) and microbial biomass C (MBC) but decreased soil metabolic quotient ( q CO2 ) compared to control treatment. A significant enhancement in rosemary growth occurred due to the improved soil quality as a result of organic fertilizers application, particularly by co-application of P. fluorescens and compost or biochar of Azolla.